Removal of methyl violet 2-B from aqueous solutions using untreated and magnetite-impregnated almond shell as adsorbents. Issue 29 (20th June 2016) - Saeed, Khalid; Ishaq, Mohammad; Sultan, Siraj; Ahmad, Imtiaz
Abstract: The magnetite-impregnated almond shell (MIAS) and untreated almond shell (UAS) were used as adsorbents for the removal of methyl violet 2B from aqueous solution. The adsorption of MV2B from water onto adsorbent surface was investigated in batch adsorption experiments to evaluate the effect of pH, contact time, adsorbent dose, initial dye concentration, and temperature, after being analyzed the surface morphology and elemental composition of the adsorbents. The adsorptions of MV2B onto both adsorbents were favorable in basic medium. The pseudo-second order represents the kinetic adsorption of MV2B on to both adsorbents. Equilibrium isotherm data were analyzed by Langmuir and Freundlich adsorption isotherms, which were best fitted to Langmuir adsorption isotherm model. The monolayer Langmuir adsorption capacities of UAS and MIAS were 29.4 and 33 mg/g, respectively. The thermodynamic parameters including entropy (Δ S ), enthalpy (Δ H ), and Gibbs free energy (Δ G ) indicated that the adsorption of MV2B on to both adsorbents was spontaneous, feasible, and endothermic.